Evaluation of poly-drug use in methadone-related fatalities using segmental hair analysis. (March 2015) - Nielsen, Marie Katrine Klose; Johansen, Sys Stybe; Linnet, Kristian
Highlights: Segmental hair analysis was applied to 99 methadone-related fatalities. Extensive poly-drug use was quantified among the deceased. Continuous exposure of methadone was revealed among the deceased. R and total methadone concentrations were closely related in both blood and hair. Abstract: In Denmark, fatal poisoning among drug addicts is often related to methadone. The primary mechanism contributing to fatal methadone overdose is respiratory depression. Concurrent use of other central nervous system (CNS) depressants is suggested to heighten the potential for fatal methadone toxicity. Reduced tolerance due to a short-time abstinence period is also proposed to determine a risk for fatal overdose. The primary aims of this study were to investigate if concurrent use of CNS depressants or reduced tolerance were significant risk factors in methadone-related fatalities using segmental hair analysis. The study included 99 methadone-related fatalities collected in Denmark from 2008 to 2011, where both blood and hair were available. The cases were divided into three subgroups based on the cause of death; methadone poisoning ( N  = 64), poly-drug poisoning ( N  = 28) or methadone poisoning combined with fatal diseases ( N  = 7). No significant differences between methadone concentrations in the subgroups were obtained in both blood and hair. The methadone blood concentrations were highly variable (0.015–5.3, median: 0.52 mg/kg) and mainly within the concentration range detected in living methadone users. In hair, methadone was detected in 97 fatalities with concentrations ranging from 0.061 to 211 ng/mg (median: 11 ng/mg). In the remaining two cases, methadone was detected in blood but absent in hair specimens, suggesting that these two subjects were methadone-naive users. Extensive poly-drug use was observed in all three subgroups, both recently and within the last months prior to death. Especially, concurrent use of multiple benzodiazepines was prevalent among the deceased followed by the abuse of morphine, codeine, amphetamine, cannabis, cocaine and ethanol. By including quantitative segmental hair analysis, additional information on poly-drug use was obtained. Especially, 6-acetylmorphine was detected more frequently in hair specimens, indicating that regular abuse of heroin was common among the deceased. In conclusion, continuous exposure of methadone provide by segmental hair analysis suggested that reduced tolerance of methadone was not a critical factor among methadone-related fatalities. In contrast, a high abundance of co-ingested CNS depressants suggested that adverse effects from drug-drug interactions were more important risk factors for fatal outcome in these deaths.